Identificación de lignanas en hojas de Rollinia mucosa (JACQ) bail. Annonaceae (ING) - Villegas, Juan R. (2001)
Ethanolic extract obtained by maceration of Rollina mucosa leaves was partitioned between hexane, chloroform and ethyl acetate. Samples of all extracts, including the  remanent hydroalcoholic extract, were diluted in ethanol to final concentration of 100μg/mL. These samples were submitted to the Brine shrimp (Artemia salina) lethality assay and only the chloroform extract showed market toxicity. This extract was purified by chromatographic methods and yielded, as mainly compounds, two known lignans: epiudesmine 2 and eudesmine 3, which were identified on the basis of spectral studies ( 1H NMR and 13C NMR). These compounds gave a very low ED50 value in the Brine shrimp lethality assay. Aporphine and oxoaporphine alkaloids have been reported in leaves of this plant, however, any alkaloids could not be detected in our extracts.